The Effect of Transformational Leadership on Organizational Performance Through Organizational Culture as Mediation - Jannah, Miftahul; Rahmawati, Sri; Komara, Acep; Belo, Joao (Journal of Accounting and Finance Management, 2025)
The service sector in Indonesia faces various operational challenges, including digitalisation, shifting customer needs, and increasingly intense competition. These challenges also open up the potential for abuse of authority, which can negatively impact organisational performance. This study aims to analyse the influence of transformational leadership on organisational performance, with organisational culture as a mediating variable. The object of the study is service companies in Indonesia, with a total of 216 respondents working in the fields of accounting or strategic financial management. This quantitative study was analysed using SPSS version 25. The findings indicate that transformational leadership has a positive and significant effect on organisational performance, yet it does not have a significant impact on organisational culture. Meanwhile, organisational culture has a positive and significant effect on organisational performance. However, organisational culture was not statistically proven to mediate the relationship between transformational leadership and organisational performance.